TINJAUAN YURIDIS PENYELESAIAN KONFLIK TENURIAL DALAM KAWASAN HUTAN SEBAGAI UPAYA MENJAGA KELESTARIAN FUNGSI LINGKUNGAN DI PERUM PERHUTANI JAWA TENGAH - Sukirno; Kartika Winkar Setya; Yuliani Catur Rini (Faculty of Social, Economics and Humanities, 2023)
The purpose of this research is to examine the handling and the resolution of tenurial conflicts in forest areas. The factors examined in this research are the regulation of prohibition and juridical consequences regarding tenure conflicts that occur in the forest area. The conflict arose due to the use and exploitation of the forest by the village community and the government. This research uses normative legal research. The approach used is the statutory approach and case approach. The results of this study are a regulation on the use of forest areas by the laws and regulations so that optimal and sustainable forest utilization is achieved at Perhutani Central of Java. The aim of resolving tenure conflicts is to restore state forest according to their status function because forest is the lifeblood of many people so forest must be reserved, one of which is through law enforcement and implementing the applicable laws and regulation at Perum Perhutani.